The Concept of Justice As A Requirement For Polygamy According To The Imam Syafi'i Mazhab - Siti Saidatina; Ahdiyatul Hidayah (Jurnal Al-Fikrah, 2023)
Nothing obligations in Islamic law that dictates his people polygamy, will but Islamic law does not forbid his people for polygamous husband can married one or more people However own condition that is Can fair to his wives. The term polygamy Already No stranger to heard ear, because Already Lots practice polygamy that happened, but that happened problem is No implementation of a sense of fairness in polygamy. A sense of fairness is prioritized in matters polygamous, because mistakes made at home ladder will can trigger dispute between One with others. Draft justice exists a number of opinion from among the ulama. Although there is differences in concepts fair in polygamy will but the ulama remained agreed that polygamous men only can maximum with four wives. This type of research uses library research or can be known as with study bibliography, that is with research various sources of books, Al-Qur'an, Hadith and several trusted journals. From this research, the author find answer about draft justice in polygamy according to Imam Shafi'i Madzhab, namely fair in giving livelihood, fair in giving place stay, and be fair in giving turn to wife.